Comparison of the relative telomere length measured in leukocytes and eleven different human tissues - Dlouha, D; Maluskova, J; Kralova Lesna, I; Lanska, V; Hubacek, J A (Physiological research, 2014)
The relative length of telomeres measured in peripheral blood leukocytes is a commonly used system marker for biological aging and can also be used as a biomarker of cardiovascular aging. However, to what extent the telomere length in peripheral leukocytes reflects telomere length in different organ tissues is still unclear. Therefore, we have measured relative telomere length (rTL) in twelve different human tissues (peripheral blood leukocytes, liver, kidney, heart, spleen, brain, skin, triceps, tongue mucosa, intercostal skeletal muscle, subcutaneous fat, and abdominal fat) from twelve cadavers (age range of 29 week of gestation to 88 years old). The highest rTL variability was observed in peripheral leukocytes, and the lowest variability was found in brain. We found a significant linear correlation between leukocyte rTL and both intercostal muscle (R=0.68, P<0.02) and liver rTL (R=0.60, P<0.05) only. High rTL variability was observed between different organs from one individual. Furthermore, we have shown that even slight DNA degradation (modeled by sonication of genomic DNA) leads to false rTL shortening. We conclude that the rTL in peripheral leukocytes is not strongly correlated with the rTL in different organs.
Keywords: Young Adult; poškození DNA; Male; Aging; Child, Preschool; DNA Damage; Telomere Shortening; mladý dospělý; leukocyty mononukleární; Adolescent; Brain; Infant; Child; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; Fetus; mladiství; novorozenec; předškolní dítě; zkracování telomer; senioři nad 80 let; plod; Leukocytes, Mononuclear; lidé; ženské pohlaví; Humans; telomery; Infant, Newborn; kojenec; stárnutí; Aged, 80 and over; mozek; Female; lidé středního věku; Telomere; Middle Aged